Voltage Dependent Effect of Spiral Wound Plasma Discharge on DBC1.2 Cellular Integrity - Abubakar Hamza Sadiq; Md Jahangir Alam; Mahedi Hasan; Farhana Begum; Tomoki Yamano; Jaroslav Kristof; Kazuo Shimizu (Plasma, 2025)
Low temperature plasmas (LTPs) generated at atmospheric pressure and room temperature have gained increasing attention in biomedical research due to their ability to control cellular behavior through the production of reactive oxygen and nitrogen species (RONS), electric fields, and UV radiation. Among several LTP configurations, dielectric barrier discharge (DBD) plasma has been extensively studied for its ability to stimulate controlled biological effects while maintaining low gas temperature, making it suitable for cell-based applications. This study designed a novel spiral-wound DBD plasma device to investigate the voltage-dependent effects of plasma discharge on DBC1.2 epithelial cells. Plasma was applied at 2 kVp-p, 3 kVp-p, and 4 kVp-p to evaluate its effect on cellular permeability, mitochondrial activity, viability, and apoptosis. FITC-dextran-70 (FD-70, MW: 70 kDa) was used as a model permeation marker to assess cellular uptake. The results showed a voltage-dependent increase in FD-70 uptake, suggesting improved plasma-assisted drug delivery. The cell mitochondrial activity, evaluated with a MT-1 MitoMP detection kit, revealed that plasma exposure at 2 kVp-p and 3 kVp-p slightly enhanced mitochondrial membrane potential (MMP), signifying increased metabolic and mitochondrial activity, whereas exposure at 4 kVp-p led to a reduction in MMP, suggesting oxidative stress and early apoptosis. Early and late apoptosis was further assessed using FITC Annexin-V and propidium iodide (PI). The results showed enhanced cell viability and a reduced apoptotic cell at 2 kVp-p and 3 kVp-p plasma exposure when compared to the control. However, at 4 kV, there was a decline in cell viability and an increase in apoptosis, suggesting a shift towards plasma-induced cytotoxicity. This study established a safe plasma exposure threshold for DBC1.2 cells and explored the potential use of a spiral-wound DBD plasma device for biomedical applications, particularly in drug delivery and cell modulation.